2011
DOI: 10.1021/jz200160b
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Strain Coupling to Surface Chemistry, Electronic Structure, and Reactivity of La0.7Sr0.3MnO3

Abstract: b S Supporting Information T he relation of surface cation chemistry and surface electronic structure to oxygen reduction reaction (ORR) kinetics remains an outstanding question to this day in the search for highly active cathodes for solid oxide fuel cells (SOFCs). While traditionally perovskite-type transition-metal oxides have been extensively investigated as SOFC cathodes, 1,2 more recent studies highlight the potential of layered oxide cathodes. 3À5 On the surface of the perovskite-structured La 1Àx Sr x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
137
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 55 publications
15
137
1
Order By: Relevance
“…Using 18 O isotope exchange depth profiling with ToF-SIMS, they measured the oxygen tracer exchange coefficient k * and tracer diffusion coefficient D * on the surfaces of these films, at temperatures ranging from 280 • C to 475 • C. They found that the surface exchange and diffusion for the film with tensile strain were about four times and 10 times faster than the film under compressive strain, respectively. These results confirmed the earlier predictions at the elementary reaction level that tensile lattice strain accelerates oxygen reduction and diffusion on the LSC (and LSM), reported by several computational studies on the same material systems [45,53]. Consistent with this, La O' et al found also that epitaxial films of LSC on a GDC/YSZ substrate showed enhanced chemical surface exchange kinetics [168].…”
Section: Strain Segregation and Reactivitysupporting
confidence: 89%
See 4 more Smart Citations
“…Using 18 O isotope exchange depth profiling with ToF-SIMS, they measured the oxygen tracer exchange coefficient k * and tracer diffusion coefficient D * on the surfaces of these films, at temperatures ranging from 280 • C to 475 • C. They found that the surface exchange and diffusion for the film with tensile strain were about four times and 10 times faster than the film under compressive strain, respectively. These results confirmed the earlier predictions at the elementary reaction level that tensile lattice strain accelerates oxygen reduction and diffusion on the LSC (and LSM), reported by several computational studies on the same material systems [45,53]. Consistent with this, La O' et al found also that epitaxial films of LSC on a GDC/YSZ substrate showed enhanced chemical surface exchange kinetics [168].…”
Section: Strain Segregation and Reactivitysupporting
confidence: 89%
“…This enables measurements at elevated temperature in an oxygen gas environment, allowing closer simulation of the real environment of SOFCs. Reversible changes in electronic structure with temperature have been observed on the (a) (b) [45,53]. These results provide insight into the strain and reactivity correlation of SOFC cathode materials.…”
Section: Transport and Reactivitymentioning
confidence: 66%
See 3 more Smart Citations